2018
DOI: 10.1097/meg.0000000000001161
|View full text |Cite
|
Sign up to set email alerts
|

Study of the influence of heme oxygenase 1 gene single nucleotide polymorphism (rs2071746) on esophageal varices among patients with cirrhosis

Abstract: The T allele of heme oxygenase 1 gene SNP polymorphism (rs2071746) is a risk factor for esophageal varices development in cirrhotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The results obtained showed that cells containing the a(-413)-(GT) 30 allele were able to significantly enhance the biological activity of Ho-1. Several studies have subsequently confirmed that the A allele is also associated with a high transcription level of Ho-1, which correlates closely with the occurrence and progression of certain human diseases, including cardiovascular, and liver diseases (58)(59)(60). a previous study reported that the aa genotype of T(-413) A could significantly reduce the occurrence of myocardial infarction and angina pectoris (61).…”
Section: Ho-1 Promoter Polymorphismmentioning
confidence: 90%
See 1 more Smart Citation
“…The results obtained showed that cells containing the a(-413)-(GT) 30 allele were able to significantly enhance the biological activity of Ho-1. Several studies have subsequently confirmed that the A allele is also associated with a high transcription level of Ho-1, which correlates closely with the occurrence and progression of certain human diseases, including cardiovascular, and liver diseases (58)(59)(60). a previous study reported that the aa genotype of T(-413) A could significantly reduce the occurrence of myocardial infarction and angina pectoris (61).…”
Section: Ho-1 Promoter Polymorphismmentioning
confidence: 90%
“…In addition, studies have shown that patients with liver cirrhosis who carry the HO-1 T allele are more likely to develop esophageal varices than those with liver cirrhosis who carry the A allele. Therefore, the T allele of the HO-1 gene SNP is a risk factor for esophageal varices in patients with cirrhosis ( 60 ).…”
Section: Association Between Ho-1 Gene Polymorphism and Clinical Diseasesmentioning
confidence: 99%
“…A previous study showed that in addition to oxidative stress, two other polymorphisms (the GTn repeat length polymorphism and c.‐413A>T [rs2071746]) may affect the expression levels of the HMOX1 gene . Longer GTn repeats and −413 T are associated with lower levels of HMOX1 gene expression and lower HO‐1 activity, which results in being susceptible to nonalcoholic fatty liver disease or oesophageal varices among patients with cirrhosis . To our knowledge, however, few studies have evaluated the role of HMOX1 polymorphisms in drug‐induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty five publications studied the vascular complications of liver cirrhosis, for portal hypertension early detection either by invasive or non-invasive procedures and predictors of bleeding (248)(249)(250), invasive management with trans jugular intrahepatic Porto-systemic shunt (251,252) and rectal ozone (253), management of portal hypertensive gastropathy (254), gastric varices diagnosis and different modalities of management and survival (255)(256)(257)(258)(259), esophageal varices from early noninvasive prediction and diagnosis (260-267), management (268)(269)(270)(271)(272)(273) and risk of rebleeding (274,275), small bowel varices (276), and portal hypertensive colopathy (277). Prediction of risk of portal vein thrombosis (278), diagnosis (201,279,280) and survival (281).…”
Section: Liver Cirrhosis and Its Complicationsmentioning
confidence: 99%